Essential and non-essential metals : carcinogenesis, prevention and cancer therapeutics - Mudipalli, Anuradha; Zelikoff, Judith T. (Humana Press, 2017)
This book aims to present current state of understanding of the role of metals in human health and disease. As it will be difficult to cover all of the metals, about two scores of them, the authors will instead provide a detailed analysis of a select set of essential (Calcium, Magnesium, Selenium, Iron, copper and Zinc) and non-essential metals (Nickel, Chromium, Cadmium and Arsenic, Tungsten and Asbestos). Each chapter will have a dedicated section focusing on the binary role that some of these metals play, their carcinogenic and cancer therapeutics, by integrating epidemiological, experimental evidence with special emphasis and focus on molecular mechanisms involved in these processes. The biological analysis will also include emerging lines of evidence such as micro RNAS, kinase families, receptors, endoplasmic, mitochondrial players and epigenetics. As part of integrating the human, experimental and mechanistic data, as well as a detailed analysis into the modes of action for different cancer outcomes will be discussed in each chapter wherever deemed feasible. These approaches are ones in which no other book in this area has attempted to do.
Includes index.
Keywords: Chemical carcinogenesis.; Metals -- Physiological effect.; Metals -- Therapeutic use.; elektronické knihy; electronic books